Innovation and Knowledge Cluster in 21st century: An Economic Manifesto for e-Learning Future (International Journal of Engineering and Computer Science, 2015)
21st Century is an information economy age for the digital revolution. The amalgamation of wireless technologies and mobile computing is ensuing in raising the edification domain. The popularity of web-based learning i.e. e-learning or m- learning opens the doors for remote education that will become triumph of future generations. With the aid of the electronic gadgets and services like 3G, 4G have led to the miracle in education reforms. Cloud computing technology helps to manage this on demand service in an efficient technique and offer excellent prospects for economic growth in developed and developing nations. A foremost advantage of this innovative learning is to reach people globally who live in remote places where there are no schools, educationalists, or libraries. The objective of this paper is to urgent reforms in the education system by the introduction of e- learning using latest technologies for the employment and economic benefits of the realm.